Cortisol, DHEA-S, and cortisol/DHEA-S ratio in association with oxidative stress in Korean adults - Park, Sat Byul (Frontiers in Endocrinology, 2025)
BackgroundOxidative stress can result from redox reactions involving hemoglobin (Hb) and nitric oxide (NO), forming toxic peroxynitrite when NO reacts with superoxide during Hb autoxidation. γ-glutamyltranspeptidase (GGT) also contributes to reactive oxygen species generation in the presence of transition metals like iron. The hypothalamic–pituitary–adrenal axis is central to the body’s stress response and immunomodulation. This study aimed to investigate the relationships between cortisol, dehydroepiandrosterone sulphate (DHEA-S), the cortisol/DHEA-S ratio, and oxidative stress markers such as Hb and GGT in a Korean population.MethodsData from 1,341 adults collected between January 2018 and March 2023 were analyzed. Sociodemographic and lifestyle data were gathered via questionnaires. Body composition, blood pressure, and metabolic variables, including cortisol and DHEA-S levels, were evaluated.ResultsThe mean age of participants was 52.6 ± 11.9 years. Higher cortisol and DHEA-S levels were significantly linked to elevated Hb and GGT levels. Conversely, the cortisol/DHEA-S ratio was negatively correlated with Hb levels. Logistic regression confirmed that higher Hb levels were associated with increased cortisol (P = 0.038) and DHEA-S levels (P < 0.001). The GGT level had no significant association with the cortisol/DHEA-S ratio.ConclusionsElevated cortisol and DHEA-S levels are associated with markers of oxidative stress in Korean adults, independent of age and body mass index.